Treatment Outcome of Posteromedial Procedure for Neglected Clubfoot in Children Older than 2 Years of Age - Report of 3 Cases - Iman Dwi Winanto (PT. Kalbe Farma Tbk., 2021)
Background: A neglected clubfoot is a clubfoot that didn’t get early or adequate treatment; it is a major problem in developing countries. The posteromedial soft tissue release procedure is one of surgical technique in clubfoot treatment. Case : Three patients with neglected clubfoot were assessed before and after treatment. All patients were treated with posteromedial soft tissue release method followed by serial application of above-knee plaster of paris for three months. Result: Two cases had good correction, one case had fair correction. Conclusion: The posteromedial soft tissue release with proper follow up and splinting result in a cosmetically normal appearance and functionally acceptable pain-free foot in neglected clubfoot in children older than 2 years of ageLatar Belakang : Neglected clubfoot merupakan clubfoot yang tidak ditatalaksana atau mendapat tatalaksana awal tidak adekuat; kondisi ini sering ditemui di negara berkembang. Prosedur posteromedial soft tissue release merupakan salah satu teknik operasi dalam tatalaksana clubfoot. Kasus : Tiga pasien neglected clubfoot ditatalaksana dengan prosedur posteromedial soft tissue release diikuti aplikasi serial plaster of paris di atas lutut selama tiga bulan. Hasil : Dua kasus menunjukkan hasil koreksi baik dan 1 kasus hasil koreksi sedang. Simpulan : Prosedur posteromedial soft tissue release dikombinasi dengan ¬follow up serta teknik splinting yang adekuat memberikan hasil kosmetik yang baik serta kaki bebas nyeri pada kasus neglected clubfoot anak berusia di atas dua tahun.